ChemInform Abstract: A 3D Aluminoborate Open Framework Interpenetrated by 2D Zinc—Amine Coordination‐Polymer Networks in Its 11‐Ring Channels. Issue 39 (23rd September 2014) - Wei, Li; Wei, Qi; Lin, Zhi‐En; Meng, Qin; He, Huan; Yang, Bai‐Feng; Yang, Guo‐Yu
Abstract Colorless block crystals of [Zn(dap)2][AlB5O10] (dap: 1, 3‐diaminopropane) are solvothermally synthesized from Al(iPrO)3, Zn(OAc)2, H3BO3, and dap dispersed in a mixture of pyridine and water (autoclave, 180 °C, 7 d; 80% yield).